Acute Necrotizing Encephalopathy of Childhood: A Multicenter Experience in Saudi Arabia - Bashiri, Fahad A.; Al Johani, Sultan; Hamad, Muddathir H.; Kentab, Amal Y.; Alwadei, Ali H.; Hundallah, Khalid; Hasan, Hamdi H.; Alshuaibi, Walaa; Jad, Lamyaa; Alrifai, Muhammad Talal; Hudairi, Abrar; Al Sheikh, Rana; et al. (Frontiers in Pediatrics, 2020)
Background: Acute necrotizing encephalopathy of childhood (ANEC) is a rapidly progressing encephalopathy characterized by fever, depressed level of consciousness, and seizures. Diagnosis depends on clinical presentation and characteristic neuroimaging findings of abnormal signal intensity involving the thalami as well as the supra and infra-tentorial areas. Treatment modalities are not well-established; empirical treatment with antibiotics and antiviral agents is the initial step, followed by steroids and immunoglobulin, as well as supportive care. Patients with ANEC have a variable prognosis, but mortality is very high. Methods: A retrospective chart review of patients diagnosed with ANEC in five tertiary centers from January 2015 to October 2018 was performed. Clinical and radiological findings, as well as the therapeutic approach and outcomes, were described. Results: Twelve children were included ranging in age from 10 months to 6 years. All patients presented with preceding febrile illness, altered level of consciousness, and seizure. Radiological features showed abnormal signals in the thalami, and five patients (41.7%) had brainstem involvement. All patients received empirical treatment with antibiotics and antiviral agents. Ten patients (83.3%) received intravenous immunoglobulin (IVIG) and IV Methylprednisolone therapy. Outcomes were variable ranging from good outcomes with minimal neurological deficits to poor outcomes and death in 25% of cases. Conclusion: ANEC is a rare fulminant disease in children. The treatment is challenging. Early interventions with the use of IVIG and IV Methylprednisolone may change the outcome; however, further studies are needed to establish a consensus guideline for the management.